2021
DOI: 10.1590/1980-549720210002.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the estimate of prevalence of smokers in small areas by Vigitel, in Belo Horizonte, Minas Gerais, Brazil

Abstract: Objective: The study aimed to validate the estimates of adult smokers determined by Vigitel for small areas, defined by the Health Vulnerability Index (IVS). Methods: The database of the Health Survey of the Metropolitan Region of Belo Horizonte (RMBH) carried out in 2010 and the data from Vigitel in the period from 2010 to 2013 were used to obtain estimates of adult smokers by IVS. With Vigitel, the estimate of smokers by IVS was obtained by the indirect estimation method in small areas. The prevalence of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Bernal et al 35 showed the external validity of the estimate of the prevalence of adult smokers calculated using the indirect estimation method on Vigitel Belo Horizonte data. This study used the Health Vulnerability Indicators (HVI) grouped into four categories to estimate the prevalence of adult smokers in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Bernal et al 35 showed the external validity of the estimate of the prevalence of adult smokers calculated using the indirect estimation method on Vigitel Belo Horizonte data. This study used the Health Vulnerability Indicators (HVI) grouped into four categories to estimate the prevalence of adult smokers in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Bernal et al 35 mostraram a validade externa da estimativa da prevalência de adultos fumantes calculada pelo método de estimação indireta nos dados Vigitel Belo Horizonte. Esse estudo utilizou o Índice de Vulnerabilidade da Saúde (IVS) agrupado em quatro categorias para estimar a prevalência de adultos fumantes em cada grupo.…”
Section: Discussionunclassified